1998
DOI: 10.1002/(sici)1097-0134(19980601)31:4<383::aid-prot5>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of an altered quaternary-structure transition in a mutant aspartate transcarbamoylase

Abstract: Time-resolved small-angle X-ray scattering (TR-SAXS) was used to monitor the structural changes that occur upon the binding of the natural substrates to a mutant version of the allosteric enzyme aspartate transcarbamoylase from Escherichia coli, in which the creation of a critical link stabilizing the R state of the enzyme is hindered. Previously, SAXS experiments at equilibrium showed that the structures of the unligated mutant enzyme and the mutant enzyme saturated with a bisubstrate analog are indistinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…29 A time-resolved scattering study of the mutant enzyme showed that 40% of the molecules exist in the R conformation during the steady-state phase in the physiological enzyme reaction with natural substrates. 11 This example, along with our results, demonstrates that no analog is a good substitute for natural substrates and that the effect of allosteric effectors might differ, depending on whether natural substrates or analogs are used.…”
Section: Kinetics Of Quaternary Structure Changesupporting
confidence: 59%
See 1 more Smart Citation
“…29 A time-resolved scattering study of the mutant enzyme showed that 40% of the molecules exist in the R conformation during the steady-state phase in the physiological enzyme reaction with natural substrates. 11 This example, along with our results, demonstrates that no analog is a good substitute for natural substrates and that the effect of allosteric effectors might differ, depending on whether natural substrates or analogs are used.…”
Section: Kinetics Of Quaternary Structure Changesupporting
confidence: 59%
“…9,10 Mutation studies, combined with structural techniques, have provided significant insights on the role of individual amino acid residues and domain interactions. 8,11 Two main models, subsequently refined in a number of subtle variations, have been developed over the last several decades to account for the regulatory properties of allosteric enzymes. The concerted model, originally proposed by Monod et al, 12 assumes an all-or-none transition with no intermediate conformation (symmetry preservation), while the sequential model by Koshland et al 13 involves multiple global states.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were thus performed in 20-30 % ethylene glycol at x5 to x10 xC, conditions in which the enzyme was shown to be still cooperative and sensitive to allosteric effectors. Using succinate, an aspartate analogue, series of time-resolved scattering patterns were recorded at various succinate concentrations which, like the titration experiments, were indicative of a concerted T to R transition, no intermediate species being detected during the course of the conformational change (Tsuruta et al 1998c). The apparent rate constant of the structural change from T to R varied between 0 .…”
Section: Structural Changes and Catalytic Activity Of The Allosteric mentioning
confidence: 97%
“…Time-resolved SAXS measurements made it possible to study the transient steady state during catalysis using the physiological substrates in saturating amounts. The steady state appears to be a mixture of 60 % T and 40% R form, which further converts entirely to R in the additional presence of ATP, thereby explaining the cooperativity for aspartate binding and the stimulation by ATP at saturating concentrations of substrates (Tsuruta et al 1998c). One (and up to now unique) mutant, D162A-ATCase, has been shown to be unable to convert to the R state in the presence of very high PALA concentration while displaying a strong response to free ATP together with a synergistic effect of the two ligands (Fetler et al 2002).…”
Section: Structural Changes and Catalytic Activity Of The Allosteric mentioning
confidence: 99%
“…Because the mutant does not show any cooperativity for aspartate as judged from activity measurements, this conformation is likely to remain inaccessible even in the presence of the natural substrates carbamoyl phosphate and aspartate, as observed with carbamoyl phosphate and succinate. This could be determined experimentally but because of the consumption of substrates by the enzyme, it would require time‐resolved SAXS measurements in which the enzyme is rapidly mixed with the substrates in the presence of ATP and the transient steady‐state conformation is recorded (Tsuruta et al 1998). However, such experiments require a higher flux than that available with the instrument used here.…”
Section: Resultsmentioning
confidence: 99%